Exchange Rate Assessment for Oil Exporters - Enders, Klaus-Stefan. (Washington, D.C. : International Monetary Fund, 2009)
While the underlying methodologies continue to be widely debated and refined, there is little consensus on how to assess the equilibrium exchange rate of economies dominated by production of finite natural resources such as the oil economies of the Middle East. In part this is due to the importance of intertemporal aspects (as the real exchange rate may affect the optimal/equitable rate of transformation of finite resource wealth into financial assets), as well as risk considerations given the relatively high volatility of commodity prices. The paper illustrates some important peculiarities of the exchange rate assessment for such natural resource producers by working through a simple two-period model that captures certain key aspects of many resource economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet